Hubungan Citra Tubuh dengan Kecemasan Berbicara di Depan Umum pada Mahasiswa Baru Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung - Rizka Diyah Asfarina; Wahyu Endang Styowati; Betie Febriana (Lembaga Pengembangan Kinerja Dosen, 2025)
A lack of self-esteem is often accompanied by nervousness when speaking in front of an audience, but a positive body image can help build confidence. Many challenges await first-year students, including adjusting to a new setting. Still, it's not always easy to perform for a live audience. In order to express themselves on campus, students need to work on their public speaking abilities. The primary objective of this research was to examine the relationship between first-year nursing students' body image perceptions and their anxiety when it comes to presenting in front of an audience. A cross-sectional approach, prevalent in quantitative research, is utilized in this study. Undergraduates from Semarang's Sultan Agung Islamic University's nursing program (class of 2024) participated in the research. A total of 157 students were selected at random. The correlation tool used in this study was Spearman's rank test. A high correlation between first-year nursing students' negative perceptions of their bodies and their anxiety when speaking in front of an audience was found among the 157 research participants (p value 0.000), according to the data analysis. Among the students, nearly half (40.8%) reported extremely low levels of body image satisfaction and nearly half (41.4%) reported extremely high levels of anxiety when it came to public speaking.